ANALISIS PERMUKAAN NANOPARTIKEL FERIT SENG BERDASARKAN ADSORPSI ISOTERM GAS NITROGEN - Kadarisman, Kadarisman; Nurhasanah, Iis (BERKALA FISIKA, 2020)
This research aims to analyze surface characteristic of zinc ferrite nanoparticles based on the N2 adsorption isotherm. The morphology and size of zinc ferrite nanoparticles were observed using a scanning electron microscope. Analysis of N2 adsorption isotherm using the Brunauer- Emmett-Teller  equation  obtained  a  specific  surface  area  of  9.78  m2/g  and  mesoporous structure.    Zinc  ferrite  nanoparticles  were  composed  of  spherical  primary  particles  with  a diameter  of  67  nm.  The  size  of  the  nanoparticles  obtained  from  the  specific  surface  area analysis was greater than the scanning electron microscope image analysis. This finding shows that zinc ferrite nanoparticles are agglomerating to form larger secondary particles.Keywords: Zinc ferrite, nanoparticle, surface area, agglomeration